1999
DOI: 10.1063/1.369357
|View full text |Cite
|
Sign up to set email alerts
|

CoFe–Cu granular alloys: From noninteracting particles to magnetic percolation

Abstract: CoFe-Cu granular films with ferromagnetic content ranging from 0.10 to 0.33 by volume were prepared by radio frequency sputtering. As-cast samples were rapidly annealed at various temperatures up to 750°C to promote the segregation of CoFe particles within the metallic matrix. Magnetic and transport properties suggested that this family of samples may be classified into three groups: ͑i͒ below about 0.20 volume content of CoFe, all samples display the typical features of a granular solid constituted by a rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 21 publications
5
26
1
Order By: Relevance
“…Values for K within 0.30-0.40ϫ10 6 erg/cm 3 and ϭ0 for all as-deposited samples have been found, in agreement with the magnetoelastic energy calculation from the axial distortion. 21 Similar results have been observed in CoFe-Cu granular films, 26 though K values were smaller (ϳ0.2ϫ10 6 erg/cm 3 ), as a consequence of a lower degree of texture with respect to the CoFe-AgCu films.…”
Section: A Microstructure and Magnetic Anisotropysupporting
confidence: 70%
See 2 more Smart Citations
“…Values for K within 0.30-0.40ϫ10 6 erg/cm 3 and ϭ0 for all as-deposited samples have been found, in agreement with the magnetoelastic energy calculation from the axial distortion. 21 Similar results have been observed in CoFe-Cu granular films, 26 though K values were smaller (ϳ0.2ϫ10 6 erg/cm 3 ), as a consequence of a lower degree of texture with respect to the CoFe-AgCu films.…”
Section: A Microstructure and Magnetic Anisotropysupporting
confidence: 70%
“…Moreover, while remanent enhancement has been widely studied in thin films and magnetic recording media, we have shown how remanence breakdown takes place in granular systems due to the stabilization of a longrange out-of-plane domain microstructure. Similar studies in CoFe-Cu samples 26 prepared under the same conditions also showed the evolution of M r /M s from 0.5 in asdeposited samples to 0.8 in annealed ones, although no remanence breakdown was observed in as-deposited samples with high x v . No out-of-plane component of the magnetization was observed after in-plane saturation, in agreement with the smaller anisotropy values and lower crystal texture displayed by these samples, 26 than those used here.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Of course, many a times, annealing at high temperatures was found to improve such phase segregation in Cu-Co alloys. As a result, tensile stress develops [38,39] leading to formation of crack within the film and ultimately to loss of structural integrity in actual practice. The phase separation tendency is found to be more evident for PC plated samples deposited from electrolyte in the presence of saccharine as shown in Fig.…”
Section: Samplementioning
confidence: 99%
“…These films are studied extensively owing to scientific and technological challenges involved [2][3][4][5]. However, due to the complexity of their microstructure, many of the physical properties of these granular films are yet to be clearly understood.…”
Section: Introductionmentioning
confidence: 99%